2022
DOI: 10.1177/09636897221105252
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in Fibrosis Diseases: From Current Findings to Future Clinical Perspectives

Abstract: Telocytes (TCs), a distinct type of interstitial (stromal) cells, have been discovered in many organs of human and mammal animals. TCs, which have unique morphological characteristics and abundant paracrine substance, construct a three-dimensional (3D) interstitial network within the stromal compartment by homocellular and heterocellular communications which are important for tissue homeostasis and normal development. Fibrosis-related diseases remain a common but challenging problem in the field of medicine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 157 publications
(236 reference statements)
0
4
0
Order By: Relevance
“…The fibrotic lung is characterized by a highly inhomogeneous mechanical microenvironment, where lung areas with preserved elasticity are contiguous to areas of the rigid lung, resulting in a peculiar mechanical behaviour during inflation, especially in terms of the stress/strain relationship. 74 The increased parenchymal stiffness of fibrotic lungs significantly affects respiratory mechanics, making the lung more fragile and prone to nonphysiological stress during spontaneous breathing and mechanical ventilation. 75 Assisted ventilatory support, one of the important respiratory support measures for ARDS patients, could improve the progression of pulmonary fibrosis.…”
Section: Tcs and Mechanical Stretchmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrotic lung is characterized by a highly inhomogeneous mechanical microenvironment, where lung areas with preserved elasticity are contiguous to areas of the rigid lung, resulting in a peculiar mechanical behaviour during inflation, especially in terms of the stress/strain relationship. 74 The increased parenchymal stiffness of fibrotic lungs significantly affects respiratory mechanics, making the lung more fragile and prone to nonphysiological stress during spontaneous breathing and mechanical ventilation. 75 Assisted ventilatory support, one of the important respiratory support measures for ARDS patients, could improve the progression of pulmonary fibrosis.…”
Section: Tcs and Mechanical Stretchmentioning
confidence: 99%
“…TCs could modulate cell‐cell communication via the Wnt signalling pathway and further promote regeneration 116 . A unique secretory cell population in human respiratory airways was identified in proximal upper airways, which termed RAS cells, could serve as a previously undescribed distal lung progenitor population by differentiating into AT2 cells rapidly, and this process was controlled by Notch and Wnt signaling 74,117 …”
Section: Anti‐fibrotic‐targets Of Tcs For Fibrosis Treatmentmentioning
confidence: 99%
“…Numerous processes related to TCs have been proposed, with some strongly substantiated by experimental data while others remain speculative. TCs play a vital role in maintaining the typical organ structure, tissue homeostasis, immune regulation, information transmission, and mechanical sensitivity through their intricate 3D network structure (Wei et al, 2022). Furthermore, TCs are integral components of stem cell niches, providing structural and paracrine support for stem cells in various organs, including the intestine, skeletal muscle, heart, lungs, and more (Rosa, Marini, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies on the vascular system have shown increasing evidence to suggest that TCs are morphologically or numerically destructed in fibrosis-related diseases, so TCs are associated with chronic inflammation and fibrosis. It is important to further study the potential roles of TCs in the onset and progression of systemic fibrosis diseases to improve the therapeutic outcomes of related diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%